"Kayıp balık Nemo"da masal işlevleri - Kavuran, Tamer.; Acar, H.mehmet (My University, 2014)
From the beginning the animated fims have been taken an important place of the movies. The animated films increased by 2000s especially with the technological progress. The 76.th Academy Award winner “Finding Nemo” which is produced by Pixar has been an important sample of animated films. As from the years that semiotic studies were acceraleted, semiotic analysis has been carried out on the braches of art. This study aims to examine the movie “Finding Nemo” by referred Propp’s approach to semiotic narrative. In the first part of the study, it’s been explained the rise of semiotics, Saussure’s percept of semiotics and Propp’s approach. The movie’s sequences are separeted and all of them are researched by the Propps thirty-one generic narratemes method.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Balık Nemo; Animasyon Filmi; Göstergebilim; Sekans